The Influence of Renaissance Art on Contemporary Light and Shadow Aesthetics - Lu, Chengyu (Transactions on Social Science, Education and Humanities Research, 2024)
During the Renaissance, the relationship between art and science was exceptionally close, as both disciplines shared the common objective of achieving beauty through harmony, symmetry, diversity, and unity, in addition to uncovering the ultimate truth. The exploration of natural sciences and the revelation of the objective laws governing the development of objects had a profound influence on artistic creation. The investigation into the alterations in natural light has given rise to a new wave of light and shadow art, and this impact has persisted until the present day, with remnants still discernible in contemporary art pieces. This article delves into the groundbreaking advancements and modifications in light and shadow composition in the works of Caravaggio, such as the lighting of the wine cellar and Rembrandt’s crowdfunded masterpiece "The Night Watch". To investigate the parallels and contrasts between the utilization of light and shadow techniques in Renaissance artworks and contemporary art pieces and photography. The Renaissance epoch marked a pivotal moment in the annals of light and shadow art, and numerous contemporary artworks are derivatively influenced by the artistic creations from that era. Including the application of stage lighting in theatrical performances, photography characterized by stark contrasts in light and shadow, and a multitude of artworks inspired by the juxtaposition of light and shadow.